Pós-colonialismo e tradução em comparação: The mystic masseur e Half a life, V.S. Naipaul - Borella, Gabriel Both (2019)
The publication of translations of postcolonial literary works is increasingly gaining space in the Brazilian publishing market. Considering this, in this work, the main objective is the articulation between Translation Studies and Postcolonial Studies through the analysis of the post-colonial novels The mystic masseur and Half a life by V.S. Naipaul and their translations into Portuguese. From this general objective, we set out five specific objectives. The first aims to explore the configuration of postcolonialism and its literature. The second is to investigate the marks of post-colonial aesthetics in Naipaul's fictional work. The third one, seeks to verify the cultural marks coming from the contexts of Naipaul’s formation in the novels The mystic masseur and Half a life. The fourth, aims to understand the issue of translating post-colonial fictional texts. The fifth, seeks to analyze the cultural transposition and marks of post-colonial aesthetics in the Brazilian translations of The Mystic Masseur and Half a Life. The methodology of the research is done in a bibliographic, exploratory and investigative way, focusing on the analysis of the source texts and their translations. There is also an interview with the translators of the works in order to understand in a better way the translation options made by them. The theoretical support will consist of works by authors such as Susan Bassnett (2002), Maria Tymoczko (2002), Gideon Toury (2012), Andre Lefevere (2007), Itamar Even-Zohar (1990), Lawrence Venuti , Douglas Robinson (2002), Mona Baker (2005) and Mirella Nunes Giracca (2013) in Translation Studies, Edward Said (1990, 2011), Homi Bhabha (2013), Stuart Hall (2003), Thomas Bonnici ), Boaventura de Sousa Santos (2008), Silviano Santiago (2000), Eduardo Coutinho (2003) and Bill Ashcroft, Gareth Griffiths and Helen Tiffin (2004) in Postcolonial Studies. Readers of Naipaul, such as Ajay K. Chaubey (2015), Edward Said (2011), and other literary critics are used to establish a critical fortune in relation to the writer. Discussions of ideological aspects in the translation of postcolonial texts and the very choice of what is translated and by whom also are questions raised by the text, as well as the challenges of translating postcolonial literary texts. Finally, it is discussed how the postcolonial discourse and the cultural elements of the original works are transmitted through translation, ascertaining possible suppression or maintenance of the postcolonial aspect of the original works in the translated works.